Synthesis of calcite-zincite nano composite materials using sol-gel auto combustion method. Issue 1 (December 2020) - Sampath Kumar, L; Shantha, V.; Naik, Chandrashekhar; Drakshayani, D. N.; Kataraki, Pramodkumar S.; Janvekar, Ayub Ahmed; Ishak, Aulia
Abstract: Calcite-Zincite nano particles were synthesized by Sol-Gel Auto Combustion (SGC) technique. Modifying nanoparticles promote numerous advantages, such as, simplicity of synthesis, small heat for breakdown, regulation above the compound structure, small budget, dependability, repeatability, and moderate synthesis situations. One of interesting study on Sol-Gel auto Combustion technique has proven massive advantages as compared to other traditional methods. Presented work follow synthesized of novel nanoparticles. Research work was focused on characterized UV visible absorption spectroscopy and FTIR. The UV visible absorption spectroscopy shows an absorption band at 214 nm, 234 nm and 372nm due to calcite/zincite nano composite particles. FTIR spectra establishes a particular Calcite - Zincite nano powder obtained the characteristic peak of carbonate group at 1414 cm-1, 868 cm-1 (CaCo3) and 477 cm-1 (ZnO).